Fault detection and predictive maintenance in IoT-based building management system using machine learning - Sabuj, Khaja Sheikh Imran; Chowdhury, Saifullah; Mehedi, Fahim Hasan; Chakraborty, Pritam; Arnob, Shafarse Simeon (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.